A survey of public central school libraries in the Bicol region, 1975-1976 - Mago, Norma Avila; Hidalgo, Namnama P.; Picache, Ursula G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1977)
The study sought to assess and give an account of the actual status, existing conditions, and prevailing problems in the central school libraries in the region. Ultimately it seeks to determine feasible innovations which could be recommended to generate change, progress and upliftment of said libraries.
The different phases of librarianship being investigated are: 1. The Book Collection; 2. The Library Facilities; 3. Library Services, Organization and Management; 4. Librarian's Educational Qualifications; and 5. Librarian's Problems.
The normative survey method of research was fully availed of in obtaining data on the existing conditions of the central school libraries being surveyed.
A questionnaire-checklist was used to elicit desired information. Visits and interviews were conducted to clarify vague answers in the questionnaire-responses. Analysis of documents and related literature was conducted to establish a basic knowledge on the principles and rationale behind library surveys.Conclusions:1. Generally, the 74 central elementary school libraries surveyed in the region are inadequate in terms of book collection in relation to enrolment size. The regional average is 1.24 books per pupil.2. In terms of distribution of books according to subject, the book collections of the central school libraries surveyed are not balanced.3. The library facilities in the central school libraries in the region are inadquate.4. Library services, organization and management in the central school libraries in the region are greatly hampered by lack of resources, facilities and supplies, hence the libraries cannot satisfy present day educational demands.5. Generally, the 74 librarians assigned in the central school libraries are professionally qualified. They possess enough background experience, training and eligibility.6. The greatest problems encountered by all the central school libraries in the region are the starkness of the library resources due to the lack of funds, and the sub-standard library facilities which impede the smooth functioning of these libraries in the Bicol region.
Mimeographed.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: School libraries--Philippines--Bicol region